Revisiting Halal industry Its Scope, Challenges and Opportunities. - Laluddin, Hayatullah; Haneef, Sayed Sikandar Shah; Md Saad, Norma; Khalid, Haniza (2019)
Halal industry has emerged as a new growth sector in international economy with fast pace of spreading especially in developed countries. Asia, Middle East Europe and especially the United States which as the major fast-growing economies of the world presents the most promising halal market. The growth of halal industry could be attributed to recognition of halal products as an alternative benchmark for quality assurance, hygiene and safety. This has triggered an increasing acceptance of halal products by non-Muslim consumers. The growing number of the Muslim population and their increased awareness about the significance of consuming halal food products and services, is another factor that has led to the development of halal industry as a global market. The vast growth of the halal industry is indicative of its broad scope, therefore, this article attempts to delineate the concept of halal in the context of its primary sources; Qur’an and Sunnah. It also explores the different segments of the halal industry and their prevalent challenges and opportunities. Some figures and facts are presented to highlight the expansion of the halal industry globally. Qualitative method using Library research is used in this study. The data and information collected from primary and secondary source as well as online sources are analyzed and conclusions drawn based on the available sources. The research concludes that halal industry provides a lucrative business opportunity for Muslims and non-Muslims alike. In view of the broad scope of the halal industry and the active participation of both Muslims and non-Muslims in it, stringent measures are needed to maintain the authenticity of halal products and their compliance with the principles of Shari’ah, hence, serving Muslims consumers` interest